Combined Phacoemulsification and Ahmed Glaucoma Drainage Implant Surgery for Patients With Refractory Glaucoma and Cataract. Issue 2 (February 2016) - Valenzuela, Felipe; Browne, Andrew; Srur, Miguel; Nieme, Carlos; Zanolli, Mario; López-Solís, Remigio; Traipe, Leonidas
Abstract : Purpose: To examine the indications, safety, efficacy, and complications of combined phacoemulsification and Ahmed glaucoma drainage implant surgery. Methods: A retrospective case review of 35 eyes (31 patients) subjected to combined phacoemulsification and Ahmed glaucoma drainage implant surgery. Demographic characteristics of the study population, indications for combined surgery, and operative and postoperative complications were recorded. Visual acuity, intraocular pressure (IOP), and number of glaucoma medications were evaluated preoperatively and postoperatively. Complete success was defined as IOP⩽21 mm Hg without medication, qualified success if IOP⩽21 mm Hg with ≥1 medications, and failure if IOP>21 mm Hg or ⩽5 mm Hg on ≥2 consecutive visits. Results: Mean follow-up was 29.5 months (range, 6 to 87 mo). The most common indication for combined surgery was a history of prior failed trabeculectomy (60%). Postoperative visual acuity improved in 30 of 35 eyes (85%) ( P <0.01) regardless of the indication for combined surgery. IOP was reduced from a mean of 24.7 to 15.0 mm Hg at the last follow-up visit ( P <0.01). The number of IOP-lowering medications was reduced from a median of 3.1 preoperatively to 1.7 at the last follow-up ( P <0.01). Overall, there were 31 eyes (89%) classified as qualified success and 4 eyes (11%) as complete success. The most common postoperative complication was a hypertensive phase in 18 eyes (51%). Conclusions: Combined phacoemulsification and Ahmed glaucoma drainage implant surgery seems to be a safe and effective surgical option, providing good visual rehabilitation and control of IOP for patients with refractory glaucoma and cataract.